Nivel de la comprensión auditiva en estudiantes de seis años de instituciones educativas públicas y privadas de Arequipa - Salas Valencia, Ximena Solange (2024)
The objective of the research was to determine if there are differences in the level of development of listening comprehension in six-year-old children from a public and a private educational institution in Arequipa. This is a comparative descriptive research, which involves validity and reliability processes through judges' criteria and Cronbach's alpha method, respectively. Scales of the Peruvian adaptation were used for the subtests (Vocabulary, Morphology and Syntax) for the age range of six years. Within the findings, comparisons were established between both groups, resulting in significant differences in relation to the development of listening comprehension according to the type of management (public and private), as well as in the components of morphology and syntax. However, no significant differences were found in the level of development of listening comprehension in the area of vocabulary among six-year-old students, according to the type of management (public and private). The importance of the results of this research lies in the educational need to promote the transversal evaluation of listening comprehension in students, in order to monitor any deficiency that may interfere with subsequent learning to receive specialized treatment.